Antipredator escape distances of common and threatened birds. (30th August 2017) - Jiang, Yiting; Møller, Anders Pape
Abstract : Flight initiation distance (the distance at which an animal takes flight when approached by a human) was hypothesized to be longer in more threatened species of birds. Threatened species had consistently longer FID than closely related species that were not threatened. This manuscript provides a link between susceptibility to human proximity and threat status, and our findings may help us better mitigate human impact on wildlife and thus help us efficiently conserve the most threatened species. Abstract: Most animals keep a safe distance from humans and other potential predators, forcing animals to trade foraging and other critical behaviors against flight with potentially negative consequences for population trends if energy budgets are consistently negative. Animals can adapt to human proximity through habituation or microevolution, and island, domesticated and urbanized animals have all reduced their threshold of fear compared to controls. We tested whether a common cause of threat status is susceptibility to human proximity. We did so by estimating whether 48 pairs of closely related bird species differing in their threat status consistently had longer flight initiation distances (FID, the distance at which the individual takes flight from an approaching human) in the more threatened species. We estimated threat status by relying on existing categorization of threat status by the European Union. Threatened species had consistently longer FID than their closely related species in both parametric and nonparametric tests. Common species were indeed more often recorded during field work while recording FID than were threatened species, the difference being almost 2-fold. This result provides a link between antipredator behavior, human proximity, threat status, and abundance.